What Drives the Productivity Change of the Korean Food Processing Industry? : A Stochastic Frontier Analysis Using Firm-Level Panel Data, 2001-2009 (한국농촌경제연구원, 2013)
This article conducts an analysis on changes in productivity in Korean major food processing industries (meat processing industry, milk processing industry, and pickle industry) with the financial data over the five years from 2001 to 2009. Measurements are obtained from the estimation of a stochastic production function. The results find that technical change and allocative efficiency have led significant productivity changes in the three industries. Especially, pickle industry experienced a higher rate of productivity growth by a greater rate of technical change and allocative efficiency. Accordingly, the technical progress and efficient resource allocation resulting from greater investment in R&D and stable supply of raw materials are required for enhancement of productivity in the Korean food processing industry.
Keywords: food processing industry; productivity growth; panel data; stochastic frontier production function; food processing industry; productivity growth; panel data; stochastic frontier production function